Large Aggressive Angiomyxoma of the Liver - Nalbant, Mustafa Orhan; Akıncı, Özlem; Sakız, Damlanur; Gümüşoğlu, Alpen Yahya; İnci, Ercan (Cerrahpaşa Medical Journal, 2023)
Aggressive angiomyxoma is an extremely rare mesenchymal tumor with a mixed component that occurs almost entirely from the pelvis and perineum. Although aggressive angiomyxoma arising from the liver is very rare, uncommon cases have also been reported in the larynx and lung. In the present study, a 37-year-old female who was admitted to our hospital with the desire of pregnancy was found to have a gigantic mass originating from the liver, and a right hepatectomy decision was made as a result of radiological examinations. Postoperative immunohistochemical findings of the resection material were compatible with aggressive angiomyxoma. Cure was achieved with resection and chemotherapy was not applied. No recurrence was detected in the follow-ups. Cite this article as: Nalbant MO, Akıncı Ö, Sakız D, Gümüşoğlu AY, İnci E. Large aggressive angiomyxoma of the liver. Cerrahpaşa Med J. 2023;47(1):108-111.